Numerical Simulation of Imported Sediment in a Stilling Basin - Wang, Rui; Li, Peng; Li, Zhanbin; Han, Jianchun; Zhu, Yubin (Frontiers in Earth Science, 2021)
Sediment accumulation at the bottom of a stilling basin can cause the untimely discharge of water from the spillway building, which can, in serious cases, lead to dam failure. This failure creates ecological and human safety hazards in downstream areas. To assess the sudden discharge and related dam failure, we created a two-dimensional two-phase flow simulation model built around the particle-based force balance equation. We compared the flow pattern and energy dissipation effect of the stilling basin under different inlet flow rates (2, 3, 4.5 and 6.75 m2/s). To study the deposition morphology, we compared bottom sedimentation under different sand discharge mass flow rates (0.1, 0.2 and 0.3 kg/s). The results show a direct relationship between energy dissipation rate and inlet single-width flow rate: as energy dissipation increases, so too does the inlet single-width flow rate. The eddy generated by the hydraulic jump is the main reason for the decrease in flow rate. Smooth flow patterns at the bottom of the stilling basin increase the likelihood of sediment deposition further from the end of the stilling basin. In addition, the average sediment deposition at the bottom of the dissipation basin is positively correlated with the inlet sediment concentration, with a correlation coefficient as high as 0.97. Based on the two-phase flow method, the simulated value has an error below 10% when compared with the theoretical value. Our simulation method can be used to estimate the magnitude of sediment deposition at the bottom of the stilling basin and aid in dam risk evaluations.